2018
DOI: 10.1590/1980-5918.031.ao33
|View full text |Cite
|
Sign up to set email alerts
|

Causes of drop out from a physical exercise supervised program specific to older adults

Abstract: Introduction: Physical exercise when performed regularly brings several health benefits, especially for older adults. However, there are barriers that induce these individuals to withdraw from exercise. Objective: This study investigated the causes of drop out from a supervised physical exercise program specific to older adults. Methods: A semi-structured questionnaire was applied by telephone contact, containing questions about their reasons for leaving the program. Demographic data were analyzed by relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Robust evidence supports that a higher level of leisure time physical activity is frequently observed among men, younger individuals, and those with higher education level 19 . The hypotheses behind this evidence involves cultural factors, namely: men participating more of collective activities, whereas women, prefer individual activities with less physical strength 20 ; lack of motivation to practice physical activity due to natural reduction of conditioning, especially from the second half of life 21 , 22 ; and practice of physical activity in other domains (occupational activity, commuting activity 23 , and household activity) competing with leisure time physical activity among individuals with a lower education level 24 . Adults with lower educational level are more likely to have lower socioeconomic status, leading to worse health outcomes compared to those with a higher educational level, a concept called educational gradient in health 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Robust evidence supports that a higher level of leisure time physical activity is frequently observed among men, younger individuals, and those with higher education level 19 . The hypotheses behind this evidence involves cultural factors, namely: men participating more of collective activities, whereas women, prefer individual activities with less physical strength 20 ; lack of motivation to practice physical activity due to natural reduction of conditioning, especially from the second half of life 21 , 22 ; and practice of physical activity in other domains (occupational activity, commuting activity 23 , and household activity) competing with leisure time physical activity among individuals with a lower education level 24 . Adults with lower educational level are more likely to have lower socioeconomic status, leading to worse health outcomes compared to those with a higher educational level, a concept called educational gradient in health 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The dropout rate during the 6-month trial was higher in the active arm of the trial than in the control arm (47 versus 21 patients). This issue is common to most trials that test physical exercise programs (3032). In our trial, the 47 patients who dropped out during the 6-month trial had similar demographic and clinical characteristics as compared with those who completed the 6-month trial (Supplemental Table 2), but bias or residual confounding in the benefit observed in the active group cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Esteves et al [13] points out that the main causes for poor adherence to the training program were lack of time, distance, lack of motivation, increased working hours and unqualified professional service. Estimating that the value / price of the monthly fee is not always a reason for dropping out, becoming the least relevant factor in this regard [14,15,16].…”
Section: Discussionmentioning
confidence: 99%